PENGARUH LAHAN, MODAL DAN TENAGA KERJA TERHADAP PRODUKSI KELAPA SAWIT DI KABUPATEN BARITO KUALA (STUDI KASUS DI KECAMATAN BARAMBAI) - MUHAMMAD TAMJIDILLAH (PPJP Universitas Lambung Mangkurat, 2018)
To know simultaneously and partial factor influencing oil palm production is done by quantitative method research. Sources of data used in the study are primary data analyzed by using multiple linear regression analysis techniques, as well as secondary data sourced from relevant agencies or agencies.To determine the number of samples conducted using census method (sample saturated) the overall respondents taken amounted to 65 people.The results of this study indicate that simultaneously (jointly) that the factors of production or dependent variables are influenced significantly by land area factors, while capital factor does not significantly influence and negatively affect the factors of production, labor factors have a positive but not influential effect significant to palm oil production factor. Partially factor of land area significantly and significant influence to palm oil production. While the capital and labor factors have no significant effect on palm oil production